2003
DOI: 10.1001/archneur.60.7.940
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Fish and n-3 Fatty Acids and Risk of Incident Alzheimer Disease

Abstract: Dietary intake of n-3 fatty acids and weekly consumption of fish may reduce the risk of incident Alzheimer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
555
2
28

Year Published

2003
2003
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 939 publications
(622 citation statements)
references
References 60 publications
24
555
2
28
Order By: Relevance
“…One of the first such studies showed that people who ate fish at least once a week had a 60% lower risk of developing AD [130] and a slower rate of cognitive decline [131]. The relationship between fat intake (both saturated and trans-unsaturated fat) and cognitive decline also appears to be linear [132], and a high intake of copper with a diet abundant in saturated and trans fats may predict an increased rate of cognitive decline [133].…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first such studies showed that people who ate fish at least once a week had a 60% lower risk of developing AD [130] and a slower rate of cognitive decline [131]. The relationship between fat intake (both saturated and trans-unsaturated fat) and cognitive decline also appears to be linear [132], and a high intake of copper with a diet abundant in saturated and trans fats may predict an increased rate of cognitive decline [133].…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…The relationship between fat intake (both saturated and trans-unsaturated fat) and cognitive decline also appears to be linear [132], and a high intake of copper with a diet abundant in saturated and trans fats may predict an increased rate of cognitive decline [133]. By contrast, total intake of n-3 polyunsaturated fatty acids may be associated with a reduced risk of AD [130]. These findings are congruent with data from animal models showing that fat intake may be related not only to vascular risks but also to a direct effect of polyunsaturated fatty acids on Aβ accumulation [134].…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…DHA is an omega-3 polyunsaturated fatty acid found in membrane phospholipids and a deficiency in this fatty acid may play a role in Alzheimer's disease. A low intake of fish (Morris et al 2003), the major dietary source of DHA, and low serum DHA levels (Kyle et al 1999) are both linked to an increase in likelihood of developing Alzheimer's disease, whereas a high intake of fish is related to a decreased risk (Morris et al 2003). Similarly, Alzheimer's patients and humans with mild cognitive impairment have lower plasma levels of DHA and a larger n-6/n-3 fatty acid ratio (Conquer et al 2000).…”
Section: Proprietary Blend Of Docosahexaenoic Acid and Phospholipidsmentioning
confidence: 99%
“…Whereas we studied a population of women who were between the ages of 27 and 44 at the outset, the Health Professionals study followed a population of men ages 44-79 at the outset. Furthermore, EPA and DHA have additional benefit among persons with chronic diseases, [40,41] which are more prevalent in the Health Professionals Follow-Up Study. Therefore, any immunosuppressive risk from high EPA and DHA intake in the elderly may have been balanced by the fatty acids' benefit in chronic disease yielding no association in the Health Professionals Follow-Up Study.…”
Section: Discussionmentioning
confidence: 99%